2018
DOI: 10.1259/bjr.20170322
|View full text |Cite
|
Sign up to set email alerts
|

The role of upper airway morphology in apnea versus hypopnea predominant obstructive sleep apnea patients: an exploratory study

Abstract: Decrease in airway volume does not signify the type of respiratory event, but significant narrowing of velopharynx in both dimensions; thus having the narrowest value below a certain level causes more apnea. Advances in knowledge: We did not find a similar study when we did a literature search, showing the relationship of apnea vs hypopnea predominance and upper airway parameters in CT in patients with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
8
2
Order By: Relevance
“…AI, apnea index; AHI, apnea-hypopnea index; HI, hypopnea index previous study evaluating the upper airway morphology by computed tomography scans reported that the apnea-predominant group showed lesser minimal anteroposterior/lateral dimensions and crosssectional area of the velopharynx than the hypopnea-predominant group. 19 However, velopharynx airway volume was not associated with the apnea or hypopnea predominance in that study. 19 In the current study, we found that preoperative tonsil grade and MMP scores were not different between the two groups.…”
Section: Postoperative Complicationscontrasting
confidence: 50%
See 1 more Smart Citation
“…AI, apnea index; AHI, apnea-hypopnea index; HI, hypopnea index previous study evaluating the upper airway morphology by computed tomography scans reported that the apnea-predominant group showed lesser minimal anteroposterior/lateral dimensions and crosssectional area of the velopharynx than the hypopnea-predominant group. 19 However, velopharynx airway volume was not associated with the apnea or hypopnea predominance in that study. 19 In the current study, we found that preoperative tonsil grade and MMP scores were not different between the two groups.…”
Section: Postoperative Complicationscontrasting
confidence: 50%
“…19 However, velopharynx airway volume was not associated with the apnea or hypopnea predominance in that study. 19 In the current study, we found that preoperative tonsil grade and MMP scores were not different between the two groups. Given that the upper airway dynamically collapses during sleep in patients with OSA, further studies using drug-induced sleep endoscopy would help clarify the difference in the dynamic airway closure patterns between the two groups.…”
Section: Postoperative Complicationscontrasting
confidence: 50%
“…Anatomically, Ozer et al evaluated OSA patients with both apnea- and hypopnea-predominance compared to non-snoring controls using computerized tomography (CT) scans [11]. They found the measurements of the soft palate were similar for both OSA groups and significantly smaller than controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, UA total area was significantly correlated with AHI improvement with treatment and is considered a factor that may influence OSA treatment and outcomes with MAD. While previous studies [54,55] reported correlations between airway linear, area and/or volume measurements, and AHI severity at baseline, Svaza et al [55] utilized only 2D measurements, Abramson et al [31] did not standardize head position during or after image acquisition, and Ozer et al [54] utilized CT scans taken in the supine position. For these reasons, the findings of those studies are not directly comparable to the present study results.…”
Section: Discussionmentioning
confidence: 99%